Vol. 510 : High Technology: Research and Applications (HTRA-2018): The VII International Conference for Young Scientists, 26–30 November 2018, Tomsk, Russian Federation; [proceedings]; IOP Conference Series: Materials Science and Engineering (2019, 2019)
Title screen